Analisis Faktor Keterlambatan Pengembalian Rekam Medis Rawat Inap Di Rumah Sakit (Literature Review) - Risma Sisni Fadilla; Puteri Fannya; Noor Yulia; Lily Widjaja (Lembaga Pengembangan Kinerja Dosen, 2024)
Prompt return of patient medical records is an important step in the health records processing workflow. Speed is the key to meeting quality processing standards. The hospital sets a deadline for returning medical records within 2x24 hours after the patient is discharged. Delays can be caused by various factors, which are classified under the 5M management elements: man, materials, machines, methods, and money. The aim of this research is to identify aspects that are the root of the problem in delays in the process of returning medical records to the hospital. The methodology used is a literature review, with analysis of 17 journal articles from the Google Scholar database. The study results showed that human factors such as staff shortages, incomplete doctor signatures, and inadequate staff educational qualifications were the main causes of delays. Material factors often result in incomplete documents. The machine factor is related to the significant distance between the inpatient department and the medical records department. Meanwhile, the method factor, namely SPO socialization has not been carried out and the implementation of job descriptions has not been maximized.